Interleukin 2 modulates ion secretion and cell proliferation in cultured human small intestinal enterocytes. Issue 5 (1st November 2001) - O'Loughlin, E V; Pang, G P; Noltorp, R; Koina, C; Batey, R; Clancy, R
Abstract : AIMS: To determine if interleukin 2 (IL-2) alters epithelial transport and barrier function in cultured human small intestinal enterocytes. METHODS: Confluent monolayers of small intestinal cells derived from duodenal biopsies were treated with IL-2 0.2–50 U/ml for 24 hours prior to study. Transport measurements were performed under short circuited conditions in Ussing chambers, with and without the secretagogues forskolin and 3-isobutyl-1-methyl xanthine (IBMX). Serosal to mucosal flux of 3 [H] mannitol (permeability) and 3 [H] thymidine uptake (proliferation) were measured. IL-2 receptor and cystic fibrosis transmembrane conductance regulator (CFTR) mRNA were identified using reverse transcription-polymerase chain reaction (RT-PCR). RESULTS: IL-2 did not alter baseline electrical parameters but caused a significant increase in cAMP dependent chloride secretion. The effect was mediated by the IL-2 receptor and paralleled a rapid increase in tyrosine phosphorylation, janus kinase 1, and signal transducers and activators of transcription (STATs) 1, 3, and 5. IL-2 significantly increased proliferation but at a lower dose than observed for enhanced secretion but did not alter permeability. IL-2 receptor β and γc chains and CFTR mRNA were identified by RT-PCR. CONCLUSIONS: IL-2 treatment enhances cAMP stimulated chloride secretion and cellular proliferation in a human small intestinal cell line expressing a functional IL-2 receptor.